"Mechanisms of receiving media discourse in the new media Interactivity and Asynchronous "A theoretical Study - Bousdah, Omar Ibrahim (Journal of Humanities & Social Sciences, 2018)
The issue of research is based on demonstrating the role and mechanisms of interactivity and asynchronous in receiving media discourse in the new media with highlighting the concepts that have made them important features of this new media، and one of the most important things that aim for: 1- Highlighting and understanding the user’s relationship with the new media. 2- Demonstrating the role of interactive as a key mechanism in receiving media discourses in the new media and in attracting users ’ interest in its applications and their influence on different social groups. In view of the nature of the research، so it relied on the analytical approach، using the semantic conclusion as a tool for analyzing، and one of the main results of the research was: 1- That the theory of receiving a prominent role in the understanding of the evolutionary processes witnessed by the uses of the new media through the employability to interpret the relationship of the receiver means and applications. 2- Becoming interactivity and asynchronous of reception as two characteristics of the new media with offering many possibilities to use advanced technological applications in good ways as: A- The mixing of different media sources. B- Focusing on the element of excitement and capturing the constant attention of the user. C-Dividing the audience of the users into different categories so they got different options to the new media and its applications and contents attention of the user. D- Easy access and retrieval of electronic content at anytime and anywhere. E- The Freedom of the user in participating in the drafting of content in the new media at the lowest cost.